2017
DOI: 10.1186/s12889-017-4622-z
|View full text |Cite|
|
Sign up to set email alerts
|

Knowledge of non-communicable diseases and practices related to healthy lifestyles among adolescents, in state schools of a selected educational division in Sri Lanka

Abstract: BackgroundBehaviors established during the adolescence have life-long consequences to the onset of non-communicable diseases (NCDs) in later life. Therefore, it is essential to understand adolescents’ knowledge and practices with the intention of developing preventive programs focusing on this age group. The objective of the study was to assess knowledge about selected NCDs, and lifestyle choices among school students aged 17–19 years in state schools of the Maharagama Educational Division, Sri Lanka.MethodsA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 21 publications
6
41
1
4
Order By: Relevance
“…A study by Gamage & Jayawardana [10] showed that the knowledge of young students and their way of life in non-communicable disease areas and primary prevention was insufficient. This emphasises the importance of developing and implementing awareness-raising programmes within this population to build a framework for non-communicable disease risk surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Gamage & Jayawardana [10] showed that the knowledge of young students and their way of life in non-communicable disease areas and primary prevention was insufficient. This emphasises the importance of developing and implementing awareness-raising programmes within this population to build a framework for non-communicable disease risk surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…3) Education of basic knowledge relating to nutrition and exercise in primary and junior high school curricula and the dissemination of awareness to the parents of children should be promoted: Primary and junior high school is a life period that establishes lifestyles [29]. Moreover, for a culture that values families, it is possible to encourage effective behavioural changes by disseminating awareness to parents and residential communities through children [29][30][31][32][33][34][35][36][37][38][39][40][41][42]. 4) Collaboration with the religious authorities is needed: The people's deep faith and devotion could help make difficult changes in behaviour.…”
Section: Plos Onementioning
confidence: 99%
“…Lack of knowledge about healthy behaviours highlights the importance of carrying out regular surveillance for risk factors, and initiating programs for the prevention of NCDs amongst adolescents. 18…”
Section: Disease and Stdsmentioning
confidence: 99%